Studies carried out on concretes produced with LC3 according to Cuban standard NC 120: 2014 - Valdés Alemán, Eilys; Díaz Cárdenas, Yosvany; Martirena Hernández, José Fernando (My University, 2019)
As part of the development strategy of the LC3 in Cuba, a procedure is developed for the preparation of concretes with different doses (H1, H2, H3, H4) according to the levels of atmospheric aggressiveness established in NC 120: 2014 "Hydraulic concrete - Specifications Concretes will be made that respond to three designs of mixtures where parameters such as cement content and water / cement ratio vary according to what is established in the aforementioned standard. The rheological and physico-mechanical behavior of concrete will be evaluated in a fresh and hardened state, for which the following tests will be carried out: Determination of the settlement by the cone of Abrams and the strength of the hardened concrete at 3, 7 and 28 days of curing. The concretes will be made with low carbon cement (LC3) up to 50% replacement of the clinker, calcined clays and limestone, and the patterns, made with Portland cement 35 (P35). Curing influence for the H1 series will be evaluated in both standard and LC3 manufactured concretes.
Keywords: Durability; Low Carbon Cement (LC3); Concrete; Cuban Norm; Exhibition Sites